An approach on the extended mentality of the contemporary peruvian - Reluz Barturén, Francisco (2012)
In the background of this article is a research that combines the philosophical perspective with aspects of the psychology of personality, seeking to recognize and interpret various understandings that we have of ourselves. In this sense, we try to understand our identity and axiology in order to project us positively in progress and personal and social development, in the context of the new society.